PENYELESAIAN KONTRAK EKSPOR MEUBEL BERDASARKAN DOCTRIN HUKUM PERDATA INTERNASIONAL (Studi Kasus di Kota Jepara) - Jufianty Trisna Putri; Aris Munandar (Private Law, 2021)
The purposes of this research are to study, examine, and find out solutions in case of disputes in terms of international civil law review in settlement of furniture export contract disputes. The methods used in this research are statutory and conceptual approaches. This research concludes that the settlement of export disputes is carried out through the National Arbitration Board (BANI). This settlement involves a third party. Countries used as third parties are countries with advanced economies so that there is no conflict of interest. On settlement through BANI, the settlement clause has existed since the agreement was made. Apart from BANI, dispute resolution can be made through the International of Camber Commerce (ICC) or the Industrial Chamber of Commerce.